Secrecy Outage Analysis in Random Wireless Networks with Antenna Selection and User Ordering - Chen, G; Coon, J (Institute of Electrical and Electronics Engineers, 2017)
This paper investigates the secrecy outage probability in the downlink with ordered user equipment (UE) based on two ordering metrics. UEs and independently acting eavesdroppers (EDs) are positioned randomly according to a Poisson point process. We consider a transmit antenna selection (TAS) scheme at the base station (BS) to enhance secrecy performance and propose two metrics to order the UEs: one based on long-term average channel gain information from the BS to the UEs, and the other based on instantaneous channel gains. We derive closed form expressions for the secrecy outage probability subject to each of these ordering policies and verify our calculations through Monte Carlo simulations. Our results show that while TAS yields a performance improvement relative to single-antenna systems, the secrecy outage probability for TAS systems actually increases with the path loss exponent. Furthermore, we show that the importance of the specific user ordering policy that is adopted in these systems is reduced for high path loss environments or situations where large numbers of antennas are employed.